The Relationship Between Women’s Eating and Their Mental Situation - Latifoglu, Gözde (2020)
This study aims to investigate the relationship of the automatic thoughts, eating attitudes, body mass index and socio-demographic attributes of women between the ages of 18-55 years. The universe of the study consisted of 356 women. The data were collected using a demographic information form, automatic thoughts scale and eating attitude test. The results show indicated that automatic thoughts increased as body mass index increased; and eating attitude increased as negative thoughts increased. The sense of inadequacy and negative self-respect scores of unemployed women were higher than those of employed women. Also, it was concluded that childless women felt more helpless and inadequate than women with a child. The results indicated that single women felt more helpless than married women; the total score of the automatic thought decreased as education level increased; the scores of helpless feeling and negative self-respect of the women having a master’s degree were lower than any other education levels. Eating attitudes of unemployed women were higher than employed women, though, body mass index of employed women was higher than unemployed women. Education level of women does not affect their eating attitudes. Body mass index decreases as education level increases. Body mass index and eating attitudes of women are not affected by the fact whether women have a child or not.